(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2013)
We analyzed 63 samples of decapod crustaceans collected between latitudes 1 º 18’N and 3 ° 12’S, on the continental slope, from 500 to 1500 meters deep. Located and identified 44 species: the Dendrobranchiata Suborder, Superfamily Penaeoidea 4 species of Suborder Pleocyemata are the Infraorder: Caridea with 18 species, Astacidea 1, Palinura 3, Anomura 11 and Brachyura 7. A key was developed for families found, as well as for the species identified. The analysis of the results in relation to zoogeographical aspects are: five species of Galapagos sub province present on the continental slope as Aristeus occidentalis, Munida hispida, Lithodes galapagensis, and Tricopeltarium corallinus Rochinia cornuta, two species considered to be restricted to the province Peru- Chile Glyphus marsupialis and Neolithodes diomedeae and expanding their distribution to the Gulf of Guayaquil. In relation to species of high economic potential are the shrimp: Haliporoides diomedeae, Nematocarcinus agassizii, and Heterocarpus hostilis and Benthesicymus tanneri of their size and volume found in this survey, another of the major groups from both nutritional and economic point of view are litodides crabs as Neolithodes diomedeae, Paralomis papillata and Paralomis otsuae that supporting a fishery in the southern cone countries. Because these matters are recommended to continue with this type of study to know our wildlife, conducting biological study of species to know whether they can withstand a removal without affecting populations throughout the centuries in this area.